2020
DOI: 10.1111/dmcn.14520
|View full text |Cite
|
Sign up to set email alerts
|

Motor behaviour in infancy is associated with neurological, cognitive, and behavioural function of children born to parents with reduced fertility

Abstract: Aim To evaluate the associations between motor development in infancy and developmental outcomes at school age. Method Participants were 195 children (99 males, 96 females; mean age [SD] 9y 3mo [3mo], range 8y 4mo–10y 11mo) born to couples whose reduced fertility was or was not treated with assisted reproductive technologies. Motor behaviour was assessed at 4, 10, and 18 months with the Infant Motor Profile (IMP). IQ, neurological optimality score (NOS), and behavioural problem scores were measured at 9 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
1
17
1
2
Order By: Relevance
“…The domain is composed of only 7 items (6 for non-walking infants) which mostly investigate the presence of tremors and non-fluent movements during the assessment. Unlike previously published data [14,15], the majority of infants in our study sample scored the same low value on this domain (75 points). Moreover, the IMP fluency at 5 months was poorly correlated to the presence of brain injury and showed no significant relation with the neurodevelopmental outcome.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The domain is composed of only 7 items (6 for non-walking infants) which mostly investigate the presence of tremors and non-fluent movements during the assessment. Unlike previously published data [14,15], the majority of infants in our study sample scored the same low value on this domain (75 points). Moreover, the IMP fluency at 5 months was poorly correlated to the presence of brain injury and showed no significant relation with the neurodevelopmental outcome.…”
Section: Discussioncontrasting
confidence: 84%
“…In 2011, they longitudinally assessed a group of preterm and full-term infants using the IMP at 4, 6, 10 and 12 months showing a high ability to predict CP at 18 months [14]. Recently, the same group demonstrated a clear relationship between developmental motor trajectories measured with the IMP and later outcome at school age [15]. These findings support the idea that the variability of an early motor repertoire could represent not only an early marker of major motor disorders but also of neurodevelopmental disorders as a whole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recently, the same group demonstrated a clear relationship between developmental motor trajectories measured with IMP and later outcome at school age. 11 These findings support the idea that variability of early motor repertoire could represent not only an early marker of major motor disorders but also of neurodevelopmental disorders as a whole.…”
Section: Introductionsupporting
confidence: 75%
“…They showed that low IMP scores predicted CP well, one study reported areas under the receiver-operating characteristic curves: 0.89–0.99 [ 109 ], the other a sensitivity of 93% and a specificity of 81% [ 110 ]. Low IMP scores also have been associated with lower IQ scores at preschool and school age [ 111 , 112 ].…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%